2001
DOI: 10.1016/s0278-4343(01)00038-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate induced temperature effects on growth performance, fecundity and recruitment in marine fish: developing a hypothesis for cause and effect relationships in Atlantic cod (Gadus morhua) and common eelpout (Zoarces viviparus)

Abstract: Effects of global warming on animal distribution and performance become visible in many marine ecosystems. The present study was designed to develop a concept for a cause and effect understanding with respect to temperature changes and to explain ecological findings based on physiological processes. The concept is based on a wide comparison of invertebrate and fish species with a special focus on recent data obtained in two model species of fish. These fish species are both characterized by northern and southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(218 citation statements)
references
References 40 publications
13
199
1
5
Order By: Relevance
“…In ectothermic species, especially fish a plethora of studies have identified mechanisms of seasonal and latitudinal cold versus warm adaptation which are suitable to modulate the capacity of aerobic metabolism. As outlined above, a rise in aerobic capacity permits maintenance of cell functions in the cold (for review Guderley, 1998;Pörtner et al, , 2001. Associated processes are rising enzyme capacities (Crockett and Sidell, 1990;Guderley, 1990;Lannig et al, 2003), increased mitochondrial or capillary densities (Sisson and Sidell, 1987;Guderley and Blier, 1988;Ressel, 2001), changes in mitochondrial structure (Gaebel and Roots, 1989;St.-Pierre et al, 1998) and/or alterations in membrane composition (Miranda and Hazel, 1996;Logue et al, 2000).…”
Section: Trade-offs In Thermal Adaptation Setting Functional Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ectothermic species, especially fish a plethora of studies have identified mechanisms of seasonal and latitudinal cold versus warm adaptation which are suitable to modulate the capacity of aerobic metabolism. As outlined above, a rise in aerobic capacity permits maintenance of cell functions in the cold (for review Guderley, 1998;Pörtner et al, , 2001. Associated processes are rising enzyme capacities (Crockett and Sidell, 1990;Guderley, 1990;Lannig et al, 2003), increased mitochondrial or capillary densities (Sisson and Sidell, 1987;Guderley and Blier, 1988;Ressel, 2001), changes in mitochondrial structure (Gaebel and Roots, 1989;St.-Pierre et al, 1998) and/or alterations in membrane composition (Miranda and Hazel, 1996;Logue et al, 2000).…”
Section: Trade-offs In Thermal Adaptation Setting Functional Limitsmentioning
confidence: 99%
“…Along the same lines of thought identifying mechanisms of temperature adaptation (Johnston and Bennett, 1996) and their contribution to adjusting and limiting both cold and heat tolerance are considered important in the light of global warming (e.g. Wood and MacDonald, 1997;Pörtner et al, 2001) and the associated shifts in geographical distribution and/or physiological performance of ectothermic animals .…”
Section: Ecological Perspectivesmentioning
confidence: 99%
“…This has become important especially with respect to recent investigations of the physiological basis of temperature dependent biogeography and a cause and effect understanding of the influence of climate change on the well-being and survival of fish and invertebrate species (e.g. [13]). …”
Section: Pelagic Fishmentioning
confidence: 99%
“…In particular, temperature and the length of the growing season strongly influence growth and the timing of maturation in fishes (e.g., Pauly 1980, Conover 1990, Pörtner et al 2001, and likely vary from the edge to the center of a species' range. ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental heterogeneity across a species' range can also drive life-history variation (Brander 2010). In particular, temperature and the length of the growing season can strongly influence growth and the timing of maturation in fish (e.g., Pauly 1980, Conover 1990, Pörtner et al 2001. Spatial variations in predation pressure (e.g., Reznick et al 1990, Benard 2004, harvesting (e.g., Jorgensen et al…”
Section: Introductionmentioning
confidence: 99%